The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/educsci10100278
|View full text |Cite
|
Sign up to set email alerts
|

Geography Teachers’ Knowledge of and Perceptions on Dyslexia

Abstract: At all levels of education, teachers are actively involved in improving students’ learning outcomes and developing their own pedagogical experience. As a consequence, the teacher’s role in managing learning difficulties is of particular importance. This research investigates secondary school geography teachers’ knowledge of and perceptions of dyslexia. For research purposes, 61 questionnaires were distributed to secondary teachers teaching geography all over Greece. The questionnaire included a total of 30 que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…It is a separate class within the school unit, which students from all over the school can attend. Those students have a diagnosis from an official Differential Diagnosis Body approved by the Greek State [9]. If there is no diagnosis, students can still attend the IC if their teachers identify unspecified learning difficulties and suggest their enrollment in a short-term intervention program.…”
Section: Introductionmentioning
confidence: 99%
“…It is a separate class within the school unit, which students from all over the school can attend. Those students have a diagnosis from an official Differential Diagnosis Body approved by the Greek State [9]. If there is no diagnosis, students can still attend the IC if their teachers identify unspecified learning difficulties and suggest their enrollment in a short-term intervention program.…”
Section: Introductionmentioning
confidence: 99%
“…Avila-Garzon et al (2021) have revealed that teachers' lack of knowledge of geospatial technologies makes it difficult to improve students' spatial ability. Therefore, if teachers apply appropriate methods and teaching materials, students will be able to develop their spatial skills (Passadelli et al, 2020).…”
Section: Introductionmentioning
confidence: 99%